2009
DOI: 10.2298/aoo0904080p
|View full text |Cite
|
Sign up to set email alerts
|

Primary diffuse large B-cell lymphoma of the breast

Abstract: Primary breast lymphoma is rare location of this disease. Diffuse large B-cell lymphoma is the most common histological subtype. We presented two cases of primary diffuse large B-cell lymphoma of the breast and reviewed a literature about this topic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…In our study, the median age was 50 years, which is comparable to the 5th decade of life published by other authors [ 7 - 11 , 14 , 15 ].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In our study, the median age was 50 years, which is comparable to the 5th decade of life published by other authors [ 7 - 11 , 14 , 15 ].…”
Section: Discussionsupporting
confidence: 86%
“…With the exception of the recently published prospective Mexican trial (Aviles) and the large study of the International Extranodal Lymphoma Study Group (IELSG) with genuine PBLs and sufficient follow-up, which identified 204 patients [ 6 ], in the literature there were only retrospective studies with a relatively limited number of patients that have provided some interesting information [ 7 - 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is typically a B cell which accounts for up to 50% of all PBL [ 1 ]. A minority of cases are follicular lymphoma, mucosa-associated lymphoid tissue lymphoma, or Burkitt lymphoma [ 5 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%